Progesterone in Peri- and Postmenopause: A Review - Regidor, P.-A. (Geburtshilfe und Frauenheilkunde, 2014)
Around 14.5 million peri- and postmenopausal women currently live in Germany. Moreover, approximately 450 000 women, each with a life expectancy of around 85 years, reach menopause every year in Germany. The challenge is therefore to find a therapy with few side effects which could improve the quality of life of women with menopausal symptoms. The aim of hormone therapy (HT) is to remedy hormone deficiencies using substances that offer the best trade-off between benefits and risks. This is where progesterone has a new and important role to play. Progesterone is one of the most important gestagens. Biologically effective progesterone formulations created with micronization techniques have been used in clinical practice since 1996. Nevertheless, up until 2003 preference was given to synthetic gestagens rather than progesterone. The increased breast cancer hazard ratio of 1.23 reported in the WHI study and of 2 given in the Million Women Study has been associated with the use of synthetic gestagens. In a comparison between synthetic gestagens and progesterone, the E3N Study showed that the transdermal administration of estrogen and progesterone did not lead to an increase in breast cancer rates (RR: 1.08). The administration of progesterone does not change the HDL/LDL cholesterol ratio. Because of its anti-mineralocorticoid effect, progesterone has no impact on carbohydrate metabolism, hemostasis, blood pressure, thrombogenicity and body weight. The administration of 200 mg/day progesterone over 12 days of a menstrual cycle or a daily administration of 100 mg combined with an estrogen are a safe and well-tolerated option to treat menopausal symptoms, with a better benefit risk profile compared to synthetic gestagens.
Keywords: hormone therapy; progesterone; menopause; menopausal symptoms